Toward a greater understanding of how service quality drives students satisfaction in higher learning institutions - Muhamad Husin, Nur Khairina; Romle, Abd Rahim; Mohd Yusof, Muhammad Suhaimi (ISLAMIC WORLD Network for Environmental Science and Technology (IWNEST Publisher), 2015)
This study intends to investigate the relationships between service quality and students satisfaction at Universiti Teknologi MARA (UiTM) Kedah, Malaysia. This study emphasizes on the service quality (SERVQUAL) instrument involving five dimensions, namely tangibles, reliability, responsiveness, assurance, and empathy that contributing to students‟ satisfaction.Hence, this study provides a knowledge to the student's decision before entered for enrolment in any university on future.